Lyme borreliosis incidence in Lombardy, Italy (2000–2015): Spatiotemporal analysis and environmental risk factors - Zanzani, Sergio A.; Rimoldi, Sara G.; Manfredi, MariaTeresa; Grande, Romualdo; Gazzonis, Alessia L.; Merli, Stefania; Olivieri, Emanuela; Giacomet, Vania; Antinori, Spinello; Cislaghi, Giuliana; Bestetti, Giovanna; Nan, Katiuscia; et al. (Ticks and tick-borne diseases, 2019)
Lyme borreliosis cases have been reported from Lombardy in northern Italy, where Ixodes ricinus is the main vector of Borrelia burgdorferi sensu lato. However, spatial and temporal variation in the incidence of Lyme borreliosis is not well understood. In the present study, based on new notified cases of Lyme borreliosis from 2000 to 2015, an average of 1.24 new cases per million residents per year was documented. New cases, georeferenced at the municipal level, were analyzed by retrospective space-time analysis (using SaTScan v. 9.3.1); and land cover, extrapolated from a Corine Land Cover dataset (using QGIS 2.8.1), was used to implement an environmental risk factor analysis. Firstly, a temporal high-risk cluster was detected in Lombardy: the relative risk of Lyme borreliosis was 3.73 times higher during 2008–2015 compared with the entire study period. Moreover, in a spatiotemporal high-risk cluster with a circular base, land cover consisting of wildland-urban interface, meadow, forest and meadow-forest transition were significantly higher compared to low-risk areas. Results of the present study demonstrate that the incidence of Lyme borreliosis is increasing in Lombardy and that environmental conditions are suitable for I. ricinus ticks infected with B. burgdorferi s.l.: citizens and health systems should be aware of Lyme borreliosis to reduce tick bites with personal protective behaviors and to avoid misdiagnosis, particularly within the area including the observed high-risk cluster. Economic resources should be invested to inform about methods to prevent tick bites, how to check people and pets after frequenting risk areas, and ways of removing the biting ticks when they are found.